Mechanistic modelling in pig and poultry production [ - Fisher, C.; Gous, R.; Morris, T. R. [ (Trevor Raymond)] (CABI, 2006)
Based on papers presented at a symposium held in 2005 in South Africa, this book brings together the academic writings on modelling concepts, problems and applications of models and looks at the development, usefulness and limitations of models in pigs nd poultry.